Energy Consumption of Self-Compacting Concrete During Mixing and Its Impact on the Yield Stress Measured in the Ready-Mix Concrete Plant - Saavedra-Flores, E; Avudaiappan-, S (Hindawi Limited, 2021)
To find the energy required during the mixing process of self-compacting concrete in a ready-mixed concrete plant and correlate the results with the yield stress of concrete. Power consumption required during the mixing of concrete is measured with a wattmeter connected to the mixing unit’s power supply. A coaxial cylinder viscometer is used to measure the yield stress of concrete. The clamp meter measures the power when the impeller rotates inside the coaxial cylinder viscometer, which is filled with concrete. When the impeller rotates in a coaxial cylinder filled with concrete, the power is measured by a clamp meter. Torque is obtained through the power relationship, which is an essential factor in determining the yield stress. The cost of a rheometer is so high that all construction industries, research institutions, and researchers cannot measure rheological parameters. Nowadays, all rheometers are automated; hence, the cost is very high. Tattersall’s approach of power requirement in mixing the concrete and calculating the yield stress reduces the complexity in determining the rheological parameter. Copyright © 2021 V. Arularasi et al.